If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = 3x + 2 Reorder the terms: -10 = 2 + 3x Solving -10 = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -10 + -3x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 -10 + -3x = 2 + 0 -10 + -3x = 2 Add '10' to each side of the equation. -10 + 10 + -3x = 2 + 10 Combine like terms: -10 + 10 = 0 0 + -3x = 2 + 10 -3x = 2 + 10 Combine like terms: 2 + 10 = 12 -3x = 12 Divide each side by '-3'. x = -4 Simplifying x = -4
| 7x-2=4x+7x+4 | | n+(-5)=1 | | -x-(10x)= | | 3x-5=-8x-5 | | (2x+4)*(x-3)=(x-1)*(2x-12) | | -4(-6+2t)=-30+t | | (2t+t-6)(2t+2t-1)= | | 120+12(30)+x=900 | | 9-4m=1 | | 3x-5=8x+5 | | 20x+5=15x+25 | | 4n-12=12n-4 | | 11n=10n+16 | | 2x+58=6x-10 | | -5(3x+4)=4x+16-7x | | 0.3x-0.5x+3=-4 | | -4x-5x= | | 9n-34=6n+5 | | m+(-5)=19 | | 5(x+4)=6(3x-2) | | 4y+xy=11 | | .75a+14=8 | | 2(1-2b)+2(1+5b)=-9+6b | | (x^4)+(41x^2)+400=0 | | 6p+(p-4)=4p | | 264-3x=42x+19 | | -36x^4+25x^3-4= | | h+(-9)=-9 | | (x^4)+(4x^2)+400=0 | | 15t+9=5t+9 | | 5b-12=14 | | 9(x-4)=72 |